2018
DOI: 10.1016/j.surg.2018.03.023
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-Effectiveness Analysis of a Pediatric Operating Room in Uganda

Abstract: The construction of a pediatric operating room in Uganda is a cost-effective and worthwhile investment, endorsing future decisions to enhance pediatric surgical capacity in the resource-limited settings of Sub-Saharan Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 21 publications
(23 reference statements)
0
19
0
Order By: Relevance
“…The scale and complexity of the factors contributing to the deficit in paediatric surgical care in LMIC is so vast that any one action—however beneficial—will only produce marginal change in shifting the burden of surgical care in children, albeit in the right direction. Studies itemising the return on investment in provision of facilities have shown impressive efficiency [6] but statistical analysis is redundant in this field of medicine because of a lack of contextual reference points and proxies need to suffice instead. Surrogates such as retention and growth of the workforce and initiatives which attempt to register the characteristics and volume of surgical disease [7] in LMIC will bring some definition against which change and impact can be measured in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The scale and complexity of the factors contributing to the deficit in paediatric surgical care in LMIC is so vast that any one action—however beneficial—will only produce marginal change in shifting the burden of surgical care in children, albeit in the right direction. Studies itemising the return on investment in provision of facilities have shown impressive efficiency [6] but statistical analysis is redundant in this field of medicine because of a lack of contextual reference points and proxies need to suffice instead. Surrogates such as retention and growth of the workforce and initiatives which attempt to register the characteristics and volume of surgical disease [7] in LMIC will bring some definition against which change and impact can be measured in the future.…”
Section: Discussionmentioning
confidence: 99%
“…40 Using the methodology described in the Disease Control Priorities 3, our group previously calculated the value of statistical life in Uganda to be 827.32 USD with an income elasticity of 1.5. 41 The economic benefit of pediatric surgery at Soroti and Lacor was calculated by multiplying the DALYs averted/year by the value of statistical life in Uganda.…”
Section: Study Outcomes and Analysismentioning
confidence: 99%
“…Previously conducted CEA on pediatric surgical interventions have demonstrated that they are highly cost-effective with regard to a country's GDP as well as the $240 threshold applied by the World Bank. 41,56 Our group previously estimated that the prevision of a pediatric operating room in Uganda had an incremental cost-effectiveness ratio of 6.39 USD per disabilityadjusted life-year averted or 397 USD per life saved. 41 Additionally, a systematic review of CEA in pediatric surgical interventions demonstrated that pediatric surgical interventions had similar cost-effectiveness ratios as standard pediatric vaccinations and bed nets for malaria prevention and were more cost-effective then multidrug antiretroviral therapy for HIV treatment.…”
Section: Investing In Pediatric Surgical Capacity Initiatives Has Large Economic Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in national datasets, informatics, and training programs [9] have improved workforce and research gaps in surgical care for children. Several policy leaders and donor groups, such as Kids OR, have made investment in surgical infrastructure for children a global health priority [10].…”
mentioning
confidence: 99%